2005
DOI: 10.1108/02644400510603069
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of 2D and/or 3D numerical modelling of reinforced and prestressed concrete structures

Abstract: Purpose -To provide an insight in one relatively simple and efficient numerical model for analysing reinforced and prestressed concrete structures, and to raise a discussion leading to the creation of one universal and robust 3D algorithm. Design/methodology/approach -A new numerical model for analysing reinforced and prestressed concrete structures is developed and main theoretical details are described to aid the understandings. The approach is clear, easily readable and the body of the text is divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…In the embedded reinforcement model [43,44], inside the concrete, we embed reinforcement independent of the finite elements mesh. For the discretisation of reinforcement, we use 1D elements by embedding them within 2D or 3D concrete elements.…”
Section: Overview Of the Numerical Methods Applied To Reinforced Concrete (Existing Knowledge In The Research Area)mentioning
confidence: 99%
“…In the embedded reinforcement model [43,44], inside the concrete, we embed reinforcement independent of the finite elements mesh. For the discretisation of reinforcement, we use 1D elements by embedding them within 2D or 3D concrete elements.…”
Section: Overview Of the Numerical Methods Applied To Reinforced Concrete (Existing Knowledge In The Research Area)mentioning
confidence: 99%
“…Instead of two-dimensional modeling, many researchers have adopted three-dimensional modeling to conduct SCA of RC buildings. 15,32,38,82 Marovic et al 83 recommended using three-dimensional models especially in HRB analysis to have the freedom in prescribing the location and geometry of all structural elements. Serror and Essam El-Din 18 reported that floors in HRB should be investigated within a complete model for the whole structure because SCA may change their internal forces.…”
Section: Finite Element Modeling Of Scamentioning
confidence: 99%
“…In the calculating procedure, if the value of the strain in each direction exceeds the prescribed maximum strain value in a Gauss point, the modulus of elasticity for that direction becomes 0, and material failure occurs in that direction. All mathematical formulations necessary for describing these procedures are defined in detail in [20][21][22].…”
Section: 12 X For Peer Reviewmentioning
confidence: 99%
“…The assumption is that the reinforcement transmits only the longitudinal tensile and compressive forces, so its behaviour can be approximated by a uniaxial stress state. In this model, a uniaxial elasto-viscoplastic model that includes potential hardening and elastic unloading is used [20][21][22].…”
Section: Numerical Model For Reinforcement Bars For Short-term Load C...mentioning
confidence: 99%
See 1 more Smart Citation